Re-exploration of all ATG genes - Kentaro Furukawa; Tamara Ginevskaia; Tomotake Kanki (Autophagy Reports)
Most autophagy-related (ATG) genes have been identified and characterized through studies using the budding yeast Saccharomyces cerevisiae. However, there are no studies that comprehensively compare the contribution of each ATG gene to non-selective bulk autophagy and various types of selective autophagy, including the cytoplasm-to-vacuole targeting (Cvt) pathway, mitophagy, reticulophagy, and pexophagy. Our recent study quantified these types of autophagy in all atg mutants and showed that (i) autophagy is not completely impaired in specific deletants such as lacking the components of the two ubiquitin conjugation-like (UBL) systems, traditionally regarded as essential for autophagy in yeast, and (ii) residual autophagic activity is especially prominent in mutants of the Atg8 UBL system, which display small autophagic body-like vesicles at a low frequency. Alongside these findings, our comprehensive analysis suggested a link between mitophagy and pexophagy, and a differential contribution of Atg proteins to cargo specificity. We discuss how our datasets are useful for future autophagy research.Abbreviations: Ape1: aminopeptidase I; ATG: autophagy related; Cvt: cytoplasm-to-vacuole targeting; ER: endoplasmic reticulum; ESCRT: endosomal sorting complex required for transport; GFP: green fluorescent protein; PI3K: phosphatidylinositol 3-kinase; UBL: ubiquitin conjugation-like.